The Influence of Intellectual Capital on The Financial Performance of Family Companies and The Role of Family as a Moderation Variable (Case Study: Family Company Listed on The Indonesia Stock Exchange in 2019-2020) - Muhammad Alfarizi Aziz (Universitas Ciputra Surabaya, 2023)
This study aims to analyze and examine the influence of intellectual capital on the financial performance of family companies with the role of the family as moderating the influence relationship. Intellectual capital is estimated using the Value Added Intellectual Coefficient (VAIC) method developed by Ante Pulic. The company's financial performance is measured by Return on Assets (ROA), Return on Equity (ROE), and Asset Turnover Ratio (ATO). Family role variables were measured using Family Ownership (OWN), Family Board of Directors (BOD), and Family Chief Executive Officer (CEO). The population in this study is a family company that is listed on the Indonesia Stock Exchange (IDX) and has information regarding the final shareholders of the company. The sample used is 98 family companies. The analytical tool used is multiple linear regression with cross section data type. The research year takes and compares 2 different years. The year 2019 aims to reflect conditions before the covid-19 pandemic and 2020 reflects conditions during the covid-19 pandemic. The results showed that intellectual capital is a positive and significant variable affecting the financial performance of family companies in crisis conditions and before the crisis. The role of the family, which was expected to strengthen the influence of VAIC on financial performance, turned out to be the opposite in some indicators.